A case of bronchial asthma as an immune-related adverse event of pembrolizumab treatment for bladder cancer: A case report. Issue 2 (14th January 2022) - Hamada, Kazuyuki; Yoshimura, Kiyoshi; Oshinomi, Kazuhiko; Hirasawa, Yuya; Ariizumi, Hirotsugu; Ohkuma, Ryotaro; Shida, Midori; Kubota, Yutaro; Matsui, Hiroto; Ishiguro, Tomoyuki; Sambe, Takehiko; Ishida, Hiroo; et al.
Abstract: Rationale: Bladder cancer is one of the most common cancers worldwide. The anti-programmed cell death protein 1 (PD-1) antibody pembrolizumab, which is an immune checkpoint inhibitor (ICI), has improved survival in bladder cancer. We report a case of bladder cancer that had a high antitumor effect with anti-programmed cell death PD-1 antibody pembrolizumab, an ICI, but asthma occurred an immune-related adverse event (irAE). Patient concerns: A 70-year-old female patient was diagnosed as unresectable bladder cancer who was indicated for ICI treatment. Diagnosis: After ICI administration as a treatment for bladder cancer, the patient had a grade 3 asthma attack. Cytotoxic T lymphocyte antigen 4 (CTLA-4) in CD4 + FOX3 + T cells was upregulated in the early phase before the development of asthma attacks. Moreover, T-cell immunoglobulin and mucin domain 3 (TIM-3) was upregulated in all memory T cells among CD4 + T cells. However, no change in the expression of TIM-3 was observed in any CD8 + T-cell subtype. In contrast, the proportion of CD161 - T helper 17 cell (Th17) cells increased. Interventions: The patient was treated with betamethasone, montelukast, salbutamol nebulization, and a combination of salmeterol (50 μg) and fluticasone (500 μg) (SFC). Outcomes: The patient's wheezing resolved, and her peak flow rate reached 100% of the predicted value; therefore, the patient continued treatment with SFC and montelukast and was discharged from the hospital. Conclusion: Increases in CTLA-4 and TIM-3 expression in CD4 + T cells (not CD8 + ), as well as an increase in Th17 cells, may reflect asthma-related inflammation activity. Immune-related adverse events during immune checkpoint inhibitor administration may be predictive markers of antitumor efficacy.